Peran Pendidikan Pelayaran dalam Meningkatkan Kinerja Keagenan Kapal - Nisa, Hanifah Aulia; Diani, Oktrianti (Jurnal Cakrawala Bahari, 2025)
The maritime industry required highly competent human resources to ensure the effectiveness and efficiency of ship agency services. Maritime education played a crucial role in equipping prospective ship agents not only with technical knowledge and practical skills, but also with essential non-technical competencies such as communication, leadership, adaptability, and problem-solving abilities. This study aimed to analyze the role of maritime education in improving the performance of ship agency services, particularly in the context of modern challenges such as digitalization, automation, environmental sustainability, and increasingly complex global trade dynamics. The research applied a qualitative method with a literature review approach, examining scientific articles, institutional reports, and empirical studies published between 2020 and 2025. Findings indicated that maritime education contributed significantly to enhancing the professionalism and performance of ship agents through the integration of updated curricula, practical vocational internships, digital literacy programs, and the inclusion of green shipping awareness in learning processes. Moreover, collaboration between educational institutions, government bodies, and maritime industries was identified as a key driver in aligning educational outcomes with market demands. Educational policies that adapted to technological and environmental transitions were proven to increase employability, service quality, and competitiveness of ship agents. In conclusion, strengthening maritime education not only improved the operational effectiveness of ship agencies but also ensured their resilience and relevance in the rapidly evolving global maritime service sector.